2011
DOI: 10.1074/jbc.m110.211029
|View full text |Cite
|
Sign up to set email alerts
|

Phenylbutyrate Up-regulates the DJ-1 Protein and Protects Neurons in Cell Culture and in Animal Models of Parkinson Disease

Abstract: Parkinson disease is caused by the death of midbrain dopamine neurons from oxidative stress, abnormal protein aggregation, and genetic predisposition. In 2003, Bonifati et al. (23) found that a single amino acid mutation in the DJ-1 protein was associated with early-onset, autosomal recessive Parkinson disease (PARK7). The mutation L166P prevents dimerization that is essential for the antioxidant and gene regulatory activity of the DJ-1 protein. Because low levels of DJ-1 cause Parkinson, we reasoned that over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(115 citation statements)
references
References 56 publications
1
112
0
2
Order By: Relevance
“…HDAC inhibitors are also known to modulate important cytoprotective pathways independent of their actions on histones, providing additional beneficial effects to therapy. For instance, 4PBA has been demonstrated to protect DA neurons, possibly via increased DJ-1 expression and the activation of the tyrosine hydroxylase promoter in the substantia nigra [79]. In another study, 4PBA was found to alter gene transcription in a number of genes associated with antioxidant enzyme chaperones, including those that are critical for cell survival [80].…”
Section: Therapeutic Approaches and Epigenetic Remodeling In Pdmentioning
confidence: 99%
“…HDAC inhibitors are also known to modulate important cytoprotective pathways independent of their actions on histones, providing additional beneficial effects to therapy. For instance, 4PBA has been demonstrated to protect DA neurons, possibly via increased DJ-1 expression and the activation of the tyrosine hydroxylase promoter in the substantia nigra [79]. In another study, 4PBA was found to alter gene transcription in a number of genes associated with antioxidant enzyme chaperones, including those that are critical for cell survival [80].…”
Section: Therapeutic Approaches and Epigenetic Remodeling In Pdmentioning
confidence: 99%
“…Secondly, histone modification is also an important mechanism of α-syn aggregation, and its effect mainly focuses on the histone acetylation [121]. Recently, the team from Freed, presented that long-term administration of a histone deacetylase (HDAC) inhibitor, phenylbutyrate, reduced α-syn aggregation in the brain and improved motor and cognitive function in aged transgenic mice expressing a tyrosine to cysteine mutant human α-syn [122]. Similarly, Valproic acid, an inhibitor of histone deacetylase, counteracted the alteration of α-syn, the death of nigral neurons and the declined levels of striatal DA in the rotenone-treated rats [123].…”
Section: α-Synuclein Aggregation and Parkinson Diseasementioning
confidence: 99%
“…Down-regulation of DJ-1 has been shown to increase the susceptibility to oxidative stress and proteasome inhibition [91,92].DJ-1 also acts as a redoxdependent chaperone molecule and inhibits α-synuclein aggregation [93]. Over-expression of DJ-1 protects against MPTP-induced neurodegeneration, indicating that the augmented expression of DJ-1 in response to the toxins is probably a helpful mechanism in fighting against the increased oxidative stress [94,95]. Knockout models of DJ-1 mice with a targeted deletion of exon 2 or insertion of a premature stop codon in exon 1 are more sensitive to toxins and oxidative stress.…”
Section: Dj-1 Gene Modelmentioning
confidence: 99%